Transfer Mispricing as an Argument for Corporate Social Responsibility - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This article presents a case for transfer mispricing as an argument for Corporate Social Responsibility (CSR). The argument builds on the position that in order to compensate for potential loss of brand image and reputation, Multinational Companies (MNCs) would be more socially responsible when they are operating in countries where the legislation and laws in place are not effective at identifying and sanctioning transfer mispricing. We first discuss the dark side of transfer pricing (TP), next we present the nexus between TP and poverty and finally we advance arguments for CSR in transfer mispricing. While acknowledging that TP is a legal accounting practice, we argue that in view of its poverty and underdevelopment externalities, the practice per se should be a solid justification for CSR because it is also associated with schemes that deprive developing countries of capital essential for investments in health, education and development programmes. Therefore CSR owing to TP cannot be limited to a strategic management approach, but should also be considered as some kind of social justice because of associated transfer mispricing practices. We further argue that, CSR by multinational corporations could incite domestic companies to comply more willingly with their tax obligations and/or engage in similar activities. Whereas, traditional advocates of CSR have employed concepts such as reputation, licence-to-operate, sustainability, moral obligation and innovation to make the case for CSR, the present inquiry extends this stream of literature by arguing that TP and its externalities are genuine justifications for CSR. We consolidate our arguments with a case study of Glencore and the mining industry in the Democratic Republic of Congo.
Keywords: F20; H20; M14; O11; 330; Corporate Social Responsibility; Transfer pricing; Extreme poverty